2011
DOI: 10.1021/ja109316p
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Secondary Structure of Individual Amyloid Fibrils of a β2-Microglobulin Fragment Using Near-Field Infrared Spectroscopy

Abstract: Amyloid fibril diseases are characterized by the abnormal production of aggregated proteins and are associated with many types of neuro- and physically degenerative diseases. X-ray diffraction techniques, solid-state magic-angle spinning NMR spectroscopy, circular dichroism (CD) spectroscopy, and transmission electron microscopy studies have been utilized to detect and examine the chemical, electronic, material, and structural properties of amyloid fibrils at up to angstrom spatial resolution. However, X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 65 publications
0
57
0
Order By: Relevance
“…For wavelengths in the IR regime this technique has already been applied to many different sample systems, e.g. for mapping of free carriers in transistors [27], determination of doping profiles in semiconductor structures and nanowires [28], mapping of the composition of polymers [29][30][31] and biological samples [32,33], measurement of strain fields due to small spectral bandshifts [34], and the excitation of plasmons in metal nanostructures and graphene layers [35,36]. For IR spectroscopic characterization of samples with unknown material composition it is desirable to have radiation sources capable of covering a large frequency range in the mid-IR regime.…”
Section: Introductionmentioning
confidence: 99%
“…For wavelengths in the IR regime this technique has already been applied to many different sample systems, e.g. for mapping of free carriers in transistors [27], determination of doping profiles in semiconductor structures and nanowires [28], mapping of the composition of polymers [29][30][31] and biological samples [32,33], measurement of strain fields due to small spectral bandshifts [34], and the excitation of plasmons in metal nanostructures and graphene layers [35,36]. For IR spectroscopic characterization of samples with unknown material composition it is desirable to have radiation sources capable of covering a large frequency range in the mid-IR regime.…”
Section: Introductionmentioning
confidence: 99%
“…However, broadband nano-FTIR spectra of protein complexes have neither been observed so far nor shown to be suitable for the analysis of their structure. Biological objects such as protein fibrils and membranes have been already studied by s-SNOM imaging at selected wavelengths2526272829 but it has not been demonstrated that the most important secondary structures—α-helical and β-sheet structures—can be identified on the level of individual protein complexes.…”
mentioning
confidence: 99%
“…By sequential imaging of the sample at different wavelengths, infrared near-field spectra can be obtained. [5][6][7][8][9][10][11][12][13][14][15] Alternatively, in nano-FTIR spectroscopy, the tip is illuminated by broadband infrared radiation and the interferometer is used as an asymmetric 16 Fourier transform spectrometer, yielding infrared near-field spectra with a spatial resolution of about 20 nm. 3,4,17,18 Importantly, the interferometric detection yields both near-field amplitude s and phase u.…”
mentioning
confidence: 99%